Context and culture: African-American elders’ experiences of depression - Black, Helen K. (Mental health, religion & culture, 2011)
The word "depression" is used in many forums, such as clinically or colloquially. Our study explored how the word is used culturally and experientially in a particular group of individuals. In this article, we examine the meaning of depression to a sample of 60 African-American men and women with varying levels of health and functional status. We presented the word depression in our interview questionnaire but did not pre-define the word, nor did anyone in the sample ask us to define it. A key finding of this article is that the way in which persons construct an experience of depression, their expression of it, and their perception of an appropriate resolution emerges from their belief system. Our data offered a window into the internal world of elders, particularly the cultural and religious beliefs and traditions that shaped their processes of defining, interpreting, and resolving depression. For this group, resolving depression meshed with the spiritual adaptive strategies, such as reliance on God, community, self, and others, that they used throughout life to deal with negative circumstances.